Evaluasi Kebijakan Kurikulum Merdeka dalam Mewujudkan Profil Pelajar Pancasila dan Menguatnya Literasi Numerasi di Sekolah Penggerak SMA Negeri Jakarta Utara - Sriyono, Sriyono; Nurmantu, Safri (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research is about the Evaluation of the Independent Curriculum Policy in Realizing the Profile of Pancasila Students and the strengthening of numeracy literacy in the driving school of North Jakarta State High School. The purpose of this study is to evaluate the independent curriculum policy in realizing the profile of Pancasila students and the strengthening of numeracy literacy. The research method used is descriptive qualitative. This research uses observation, interviews, and documentation as tools to collect data. The results of this study indicate the success of the Merdeka Curriculum in realizing the profile of Pancasila students and strengthening numeracy literacy in students effectively, efficiently, adaptively, equitably, responsively and according to the demands of needs. In intracurricular learning, the process takes place efficiently or saves time, energy and costs because the discussion of the material is in accordance with learning outcomes. The Strengthening Pancasila Profile Project is less efficient, because it takes up to 25% of the time allocated for the overall curriculum schedule